2003
DOI: 10.1046/j.1365-201x.2003.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced HSP27, HSP70 and MAPK responses in human skeletal muscle

Abstract: These data indicate that the PX HSP and mitogen-activated protein kinase responses are exercise-specific and local, not systemic. Further, only the resistance exercise induced HSP expression (protein and mRNA) and JNK/ERK activation at 48 h PX, suggesting that these molecules may be important to long-term skeletal muscle adaptations such as hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
101
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 48 publications
(160 reference statements)
7
101
2
1
Order By: Relevance
“…An increased amount of HSP27 and HSP70 on both the mRNA and protein level after eccentric exercise has been found by others (47,48,50). We found increased mRNA levels of HSP27 and ␣B-crystallin, but our data do not support a substantial increase in protein levels of HSP27.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…An increased amount of HSP27 and HSP70 on both the mRNA and protein level after eccentric exercise has been found by others (47,48,50). We found increased mRNA levels of HSP27 and ␣B-crystallin, but our data do not support a substantial increase in protein levels of HSP27.…”
Section: Discussioncontrasting
confidence: 56%
“…In support of this assumption, we found increased protein levels of HSP70 in the days after exercise and a positive correlation between reduced force-generating capacity immediately after exercise and the increased HSP70 levels. Thus, with increasing initial damage, correspondingly more HSP70 for refolding of denatured proteins and for correct folding of newly synthesized proteins is required (36,46,48). The increased amount of HSP70 molecules found in the myofibrillar fraction at 96 h after exercise could indicate that HSP70 play a role in the assembly and incorporation of new proteins in the myofibrillar framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…156,157 However, a significant effect of exercise on HSP70 protein expression in human skeletal muscle has been observed as early as 8 h post exercise 158 and expression remains elevated up to 7 d after exercise termination. [158][159][160][161][162][163][164][165][166] When examining exercise training effects on HSP70 protein expression in humans, it has been shown that a 7-d heat acclimation protocol consisting of 2 50-min exercise bouts in a warm environmental chamber elevates subjects' core temperature to 39 C and results in a significant increase in HSP70 protein expression in peripheral leukocytes at 4-h post-exercise. 144 Similarly, a 10-d acclimation program involving treadmill walking or running in a hot environment augments HSP70 content in peripheral blood mononuclear cells.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 99%
“…Resistance 3 x 10 @ 70% 1-RM 1) H-CHO 2) L-CHO ERK-P 1) 120% 2) 120% p90 RSK-P 1) 290% 2) 550% Resistance 4 x 10 @ 80% 1-RM 1) BCAA 2) water ERK-P -700% p38-P -400% (no effect with BCAA) Nielsen et al (2003) Cycle 20 min @ 80% VO 2peak 1) Sed 2) Trained ERK-A 1) 40% 2) 38% p38-P 1) 1000% 2) 950% Thompson et al (2003) 1) 50 eccentric contractions 2) 30 min -10% downhill treadmill ERK-P 1) 200% 2) -53% ERK-T 1) 424% 2) no change Thong et al (2003) 60 min 1-leg kicks (alt 5 min @ 75 & 100% PWC) p38-P up 40% compared with rest leg Williamson et al (2003) Resistance 3 x 10 (KE) @ 70% 1-RM 1) old 2) young ERK-P 1) -48% 2) 75% p90-P 1) -60% 2) 100% p38-P 1) -17% 2) 18%…”
Section: Creer Et Al (2005)mentioning
confidence: 99%